The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4236/aces.2013.31011
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydrazine Hydrate in the Synthesis of Octa(aminophenyl)silsesquioxane (OAPS) Poss

Abstract: Octa(aminophenyl)silsesquioxane (OAPS) was prepared from octaphenyl silsesquioxane (OPS) in two steps, first nitration to obtain Octa(nitrophenyl)silsesquioxane (ONPS) then reduction by using the stable, inexpensive, and readily available hydrazine hydrate as the reducing agent in the presence of Iron(III)Chloride catalyst with a yield of around 87%. Hydrazine is a two-electron reducing agent whereas nitro group is a four-electron reduction process. The activated carbon serves as an adsorbent and electrical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The main synthesis route for OAPS is by nitration of octaphenylsilsequioxane (OPS) to first form octa(nitrophenyl)silsesquioxane (ONPS), followed by a reduction to transform the -NO 2 into -NH 2 groups. 33,41,42 It was first reported that this synthesis led to a mixture of 50% of the meta isomer and 50% of the para isomer without any ortho substitution. 33 This was later confirmed by several groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main synthesis route for OAPS is by nitration of octaphenylsilsequioxane (OPS) to first form octa(nitrophenyl)silsesquioxane (ONPS), followed by a reduction to transform the -NO 2 into -NH 2 groups. 33,41,42 It was first reported that this synthesis led to a mixture of 50% of the meta isomer and 50% of the para isomer without any ortho substitution. 33 This was later confirmed by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…48 This approach is thus able to better control the proportions of the isomers but its downside is that, up to now, the cage sizes seem to be less well controlled than in the nitration/reduction route from OPS to OAPS. 33,41,42 In the present molecular screening work, the goal is to clearly assess the effects of the various isomers and their resistance under harsh conditions. As such, the metaOAPS, paraOAPS and orthoOAPS were all considered as separate inorganic precursors along with the PMDA, 6FDA and ODPA dianhydrides as organic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…These four bands mainly originated from PEGA [ 41 ]. Two bands at 1350 and 1240 cm −1 are related to the symmetric and asymmetric C-N stretching vibration of the hydrazine component [ 42 ]. A slightly weak band at 1450 cm −1 might be related to the aromatic C-H stretching vibration and a weak band at 945 cm −1 could be related to the C=C bending vibration.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this route has only been explored once for OAPS, using separately the meta and para isomers of aminophenyltrialkoxysilanes [ 49 ]. It does lead to isomer-specific OAPS, but the cage sizes are not as well controlled as in the nitration/reduction route [ 38 , 44 , 49 , 50 ]. The OAPS under study in this paper are based on the silane precursor route, i.e., each of the three isomers is considered separately in its pure form ( Figure 1 a) in order to clearly assess the effects of the substitution position.…”
Section: Introductionmentioning
confidence: 99%